Developing Student Information and Communication Technology (ICT) Literacy Through Teacher and Library Collaboration - Nurpratiwi, Suci; Romli, Nada Arina (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to determine the development of Information and Communication Technology (ICT) literacy carried out by teachers, libraries, or collaboratively between the two. The research uses a qualitative approach with the type of case study. Data was collected by direct observation, interviews, and documentation techniques. The results showed that students' ICT literacy was developed using the Inquiry-Based Learning and Evidence-Based Practice model approaches in learning; the library provides printed and digital information resources, helps students access information, and implements library programs. Collaboration between teachers and libraries to develop students' ICT literacy is through the guardianship program.